Theology from listening : finding the core of liberal Quaker theological thought - Grant, Rhiannon (Brill research perspectives. Quaker studies., 2020)
In 'Theology from Listening: Finding the Core of Liberal Quaker Theological Thought', Rhiannon Grant explores the changes and continuities in liberal Quaker theology over the twentieth and early twenty-first centuries in multiple English-speaking Quaker communities around the world. The work involves a close analysis of material produced by Quaker meetings through formal, corporate methods; of material produced by individuals and small groups within Quaker communities; and of writing by individuals and small groups working primarily within academic or ecumenical theological settings. It concludes that although liberal Quaker theology is diverse and flexible, it also possesses a core coherence and can meaningfully be discussed as a single tradition. At the centre of liberal Quaker theology is the belief that direct, unmediated contact with the Divine is possible and results in useful guidance.